The unprecedented coupled ocean-atmosphere summer heatwave in the New Zealand region 2017/18: drivers, mechanisms and impacts - Salinger, M James; Renwick, James; Behrens, Erik; Mullan, A Brett; Diamond, Howard J; Sirguey, Pascal; Smith, Robert O; Trought, Michael C T; Alexander, Lisa; Cullen, Nicolas J; Fitzharris, B Blair; Hepburn, Christopher D; et al. (Environmental research letters, 2019)
During austral summer (DJF) 2017/18, the New Zealand region experienced an unprecedented coupled ocean-atmosphere heatwave, covering an area of 4 million km2. Regional average air temperature anomalies over land were +2.2 °C, and sea surface temperature anomalies reached +3.7 °C in the eastern Tasman Sea. This paper discusses the event, including atmospheric and oceanic drivers, the role of anthropogenic warming, and terrestrial and marine impacts. The heatwave was associated with very low wind speeds, reducing upper ocean mixing and allowing heat fluxes from the atmosphere to the ocean to cause substantial warming of the stratified surface layers of the Tasman Sea. The event persisted for the entire austral summer resulting in a 3.8 0.6 km3 loss of glacier ice in the Southern Alps (the largest annual loss in records back to 1962), very early Sauvignon Blanc wine-grape maturation in Marlborough, and major species disruption in marine ecosystems. The dominant driver was positive Southern Annular Mode (SAM) conditions, with a smaller contribution from La Niña. The long-term trend towards positive SAM conditions, a result of stratospheric ozone depletion and greenhouse gas increase, is thought to have contributed through association with more frequent anticyclonic 'blocking' conditions in the New Zealand region and a more poleward average latitude for the Southern Ocean storm track. The unprecedented heatwave provides a good analogue for possible mean conditions in the late 21st century. The best match suggests this extreme summer may be typical of average New Zealand summer climate for 2081-2100, under the RCP4.5 or RCP6.0 scenario.